Knowledge and perceptions of brucellosis in the pastoral communities adjacent to Lake Mburo National Park, Uganda - Kansiime, Catherine; Mugisha, Anthony; Makumbi, Fredrick; Mugisha, Samuel; Rwego, Innocent B.; Sempa, Joseph; Kiwanuka, Suzanne N.; Asiimwe, Benon B.; Rutebemberwa, Elizeus (BMC Public Health, 2014)
Brucellosis is one of the most common zoonotic infections globally. Lack of knowledge about brucellosis may affect the health-seeking behavior of patients, thus leading to sustained transmission in these communities. Our study assessed knowledge and perceptions of brucellosis among pastoral communities adjacent to Lake Mburo National Park (LMNP), Kiruhura District, Uganda. Methods: A community cross-sectional questionnaire survey involving 371 randomly selected household heads from three sub-counties neighboring LMNP were interviewed between June and August 2012. Data collected included communities’ knowledge on causes, symptoms, transmission, treatment, prevention and risk factors of brucellosis. Multivariable logistic regression analysis was performed to explore strength of association between overall knowledge of brucellosis and various individual factors using odds ratios and 95% confidence intervals. Results: Only 70 (19%) knew the symptoms of brucellosis in animals, and three quarters (279, 75.5%) mentioned joint and muscle pain as a common symptom in humans. Almost all participants (370, 99.3%) had ever heard about brucellosis, majority (311, 84.7%) believed it affects all sexes and two thirds (67.7%) of the respondents believed close proximity to wildlife contributes to the presence of the disease. Almost all (352, 95.4%) knew that brucellosis in humans could be treatable using modern drugs. The main routes of infection in humans such as consumption of unpasteurized dairy products were known by 97% (360/371); eating of half-cooked meat by 91.4% and eating contaminated pasture in animals by 97.4%. There was moderate overall knowledge of brucellosis 197 (53.1%). Factors associated with higher overall knowledge were being agro-pastoralists (aOR: 2.08, CI: 1.17-3.71) compared to pure pastoralists while those who reported that the disease was a health problem (aOR: 0.18, CI: 0.06-0.56) compared to those who said it was not were less likely to be knowledgeable. Conclusions: There was moderate overall knowledge of human and animal brucellosis among the participants. Majority of the participants believed that close proximity to wildlife contributes to the presence of the disease in the area. There is a need for collaboration between the public health, veterinary and wildlife sectors to provide health education on brucellosis for better management of the disease in the communities.
Keywords: Knowledge; Perceptions; Brucellosis; Pastoral communities; Lake Mburo National Park; Uganda